The anxiety of patients in the preoperative period of heart surgery and the role of the nurse (Research, Society and Development, 2023)
The study consisted of six articles selected from databases of VHL, SOBECC, ILACS, and Revistas de Enfermagem. The results were presented through flowcharts and absolute and relative foundations on the subject. This study has as its object the assistance of the Nurse in front of the patient with anxiety in the cardiac preoperative period. The objective was largely achieved through the material found. Objectives: To identify the anxiety experienced by patients in the preoperative period of cardiac surgery. and, what is the nurse's role in the face of this patient's anxiety. Method: it was an integrative review study of the exploratory descriptive type, with a qualitative approach, which was developed between October and November 2022. Conclusion: The high values ​​of anxiety, corroborating with other research, indicate that nurses should include the investigation of anxiety in its assessment, either through validated general instruments or, mainly, through the use of the nursing diagnosis and the defining characteristics. Research is needed with a larger number of subjects to be studied for a longer period, aiming to evaluate the psychological aspects involved in the cardiac preoperative period and to be able to offer means of surveillance that help the Nursing and multidisciplinary team in the care of cardiac patients.